(untitled) (Research, Society and Development, 2022)
Objective: To report a case of multiple esclerosis with an atypical manifestation in terms of initial signs and symptoms, age group and gender. Methodology: Case report based on the medical Record of a patient who whas hospitalized at the Hospital Policlínica de Pato Branco, in the municipality of Pato Branco, Paraná, due to a unilateral oculomotor nerve paralysis, subsequently diagnosed with multiple sclerosis. Case description and discussion: The afore mentioned case started with convergente strabism, diplopia and palpebral ptosis, in the right eye, characterizing paralisy of the III cranial nerve on the right, without other associated signs or sympotms. Investigation by magnetic ressonance and CSF analysis was performed. Multiple sclerosis is a demyelinating disease that impairs the transmission of nerve impulses, resulting in the most diversal clinical manifestations, according to the area of the central nerbous system that is affected and affects mainly young and white womem, between the thurd and fourth decades of life, typically starting with an acute or subacute picture of visual sensivity changes. Conclusion: Adding the clicinal findings to the complementary exams, it was possible to infer the diagnosis of multiple sclerosis, even being a patient with atypical atypical manifestation in terms of initial signs and symptoms, age group and gender.